The Influence of Transformational Leadership, Organizational Culture, and Achievement Motivation on Teacher Performance through Self-Efficacy among Elementary School Teachers in Temanggung District - Esti Dwinarniyati; Suwito Eko Parmono; Sugi (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of transformational leadership, organizational culture, and achievement motivation on teacher performance through self-efficacy as a mediating variable among public elementary school teachers in Temanggung District. The research background is based on the 2024 Temanggung Education Report, which indicates a decline in numeracy skills and learning quality, with overall learning quality categorized as moderate. A quantitative approach was employed using path analysis with SPSS version 22, involving 185 public elementary school teachers in Temanggung Regency as the research respondents. The results show that transformational leadership, organizational culture, achievement motivation, and self-efficacy have a significant effect on teacher performance. Achievement motivation was found to have the strongest influence on self-efficacy. Furthermore, the mediation analysis indicates that self-efficacy mediates the relationship between achievement motivation and teacher performance, but does not mediate the effects of transformational leadership or organizational culture. These findings emphasize that internal factors such as motivation and self-efficacy, as well as external factors such as leadership and organizational culture, play a crucial role in enhancing the professionalism and performance of public elementary school teachers in Temanggung District.